Unleashing the Potential of Biochar Composite as Organic Nutrient Source: Implications as Soil Ameliorant, Seed Yield, and Physiological Attributes of Helianthus annuus L. - Ume Laila; Aisha Nazir; Firdaus-e- Bareen (Scientifica)
Agriculture needs a reduced dependency on synthetic chemical fertilizers and renewable biomaterials to add nutrients to soil, ameliorating degraded soil and gaining agronomic yield of crops. Biochar mixed with inorganic fertilizer has been effective in improving the crop yield. However, the influence of composite biochar (C-BC) obtained from poultry feathers (PFs), cow bones (CBs), and rice straw (RS) waste streams as sources of N, P, and K, respectively, is still unclear. This study aimed to unveil a tripartite relationship of biochar composite applications with soil properties and agronomic attributes of sunflower var. orisun. Biochars associated with nutrient acquisition were characterized through Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and energy dispersive x-ray (EDX) spectroscopy. To assess the bioavailability of nutrients and their impact on agronomic yield, a greenhouse trial was set up with sunflower, using each biochar individually as well as in composite application at three levels of amendments (0%, 2%, 4%, and 6% w/w) along with commercial fertilizer. The surface characterization through FTIR, SEM, and EDX of each biochar illustrated the presence of a wide range of functional groups, porosity, and multiple nutrients. C-BC showed a significantly positive response to soil properties and exhibited the high availability of nutrients (N, P, and K) in soil as compared to commercial fertilizer. Application of C-BC at 4% was found effective for dry biomass (47 g) and seed yield (35.16 g), resulted in oil and protein concentrations as high as 44.8% and 23.5%, respectively. Feather-derived biochar (PF-BC), bone char (CB-BC), and RS-derived biochar (RS-BC) in the form of biochar composite can become an applicable substitute for chemical fertilizer in sustainable agriculture.